2020
DOI: 10.1007/s00392-020-01782-y
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of soluble angiotensin-converting enzyme 2 concentrations in adult patients with complex congenital heart disease

Abstract: Background Angiotensin-converting enzyme (ACE) 2 is known to be a functional receptor for SARS-CoV-2 in the current pandemic. Soluble ACE2 (sACE2) concentrations are elevated in patients with various cardiovascular disorders including heart failure. Methods In a total of 182 consecutive adult patients with complex congenital heart disease (CHD) and 63 healthy controls, sACE2 concentrations were measured in serum using the Human ACE2® assay by Cloud-Clone Corporation and associated with clinical, laboratory an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The reason for this discrepancy could be explained by the enhanced ADAM17 expression and activity in pathologic conditions, which corresponds to the increase of sACE2 concentration in plasma samples [ 30 , 51 ]. sACE2 concentration increases in patient cohorts with heart failure, mostly in males, and in patients with worse New York Heart Association functional class (NYHA) [ 18 , 51 , 52 , 53 ]. In patients with CVDs, the relation between the reduction of ACE2 protein on membranes and the susceptibility toward SARS-CoV-2 is still unclear.…”
Section: Does Ace2 Influence Probability Of Sars-cov-2 Infection and Worse Outcome?mentioning
confidence: 99%
“…The reason for this discrepancy could be explained by the enhanced ADAM17 expression and activity in pathologic conditions, which corresponds to the increase of sACE2 concentration in plasma samples [ 30 , 51 ]. sACE2 concentration increases in patient cohorts with heart failure, mostly in males, and in patients with worse New York Heart Association functional class (NYHA) [ 18 , 51 , 52 , 53 ]. In patients with CVDs, the relation between the reduction of ACE2 protein on membranes and the susceptibility toward SARS-CoV-2 is still unclear.…”
Section: Does Ace2 Influence Probability Of Sars-cov-2 Infection and Worse Outcome?mentioning
confidence: 99%
“…20 Some studies have shown positive prognostic results with the use of human recombinant sACE2 in COVID-19. 10,21 However, previous studies suggest that high blood ACE2 concentration is associated with COVID-19 severity 10,22 and also some comorbidities 22,23 that influence the prognosis of COVID-19. 5, 24 Ciaglia et al 7 speculated that the reason for these paradoxes may lie in posttranslational events that regulate protein levels and their balance between membrane-bound and soluble forms of ACE2.…”
Section: Discussionmentioning
confidence: 99%
“…On the 5th day, patients with moderate disease had higher CRP, D-dimer, and troponin levels than mild and asymptomatic patients. In several studies, extremes of age, 28 male sex, 5 obesity, 25 comorbid conditions, 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 high inflammatory markers (ferritin, CRP, procalcitonin, D-dimer, B-type natriuretic peptide and IL-6) 5 25 28 increased viral loads, 29 immune system genetic defects, 30 immunocompromised status, and lymphopenia 5 were identified as factors associated with COVID-19 severity in children. In a nationwide cohort study, children with confirmed COVID-19 were older and had higher rates of obesity compared with children with negative tests.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, high sACE2 could be a risk factor for severe COVID-19. We have demonstrated that sACE2 concentration in serum was associated with the severity of congenital heart diseases and heart failure in adults [16].…”
Section: Introductionmentioning
confidence: 88%